The Continuous Construction of the Teaching Ethos: Weaving Possibilities Between Theory, Practice, and Playfulness in Early Childhood Education (Interdisciplinary Studies Journal, 2024)
This study originated from an investigation carried out in the fields of Early Childhood Education Internship I and II and Education and Playfulness in a Municipal Early Childhood Education School in Belém/PA. The following guiding question was formulated: a) Is the offering of continuing education capable of bridging theory and practice to help with the lack of praxis among teachers in inclusive early childhood education? The aim was to understand how inclusion occurs through continuing education in an early childhood education school and how to contribute with inclusive playful resources. To achieve this, qualitative research was conducted, initially bibliographical and documentary, followed by the use of a questionnaire as a research instrument. The results showed that there is still much to be done for the promotion of inclusive education, and the gaps between theory and practice continue to persist.
Keywords: Internship in Early Childhood Education; Inclusive Education; Playfulness; Continuing Education